IMPROVING STUDENTS’ SPEAKING SKILL BY USING MULTIMEDIA PRESENTATION STRATEGY - Muhammad Lukman Syafii; Alip Sugianto; Nanang Cendriono (University of Kuningan, 2019)
Multimedia presentation strategy is one of strategies that can be used for developing students’ speaking skills. Therefore, this research is intended to describe how multimedia presentation strategy can improve the eighth graders’ speaking skills. A collaborative classroom action research design was employed in this research. This action research was conducted in four main steps, namely planning, implementing, observing, and reflecting. To collect the data, some instruments, i.e. students’ oral performance test, the observation checklist, field notes, and questionnaire, were used. The result showed that the students’ speaking performance improved from 64.29% in Cycle 1 to 100% in Cycle 2. Meanwhile, the students’ involvement has achieved the criteria of success (100% of students) in Cycle 1. Here, they could fulfill at least 2 out of 4 indicators in Cycle 1 and Cycle 2. In addition, the students’ perception towards the implementation of Multimedia Presentation strategy was 94.29% and only 5.71% of students who were not interested in the implementation of Multimedia Presentation strategy in teaching speaking skills. Hence, it can be concluded that Multimedia Presentation strategy can improve students’ speaking skill.